Metode RAD Pada SIKEPALA (Studi Kasus Kepolisian Resor Ciamis) - Dini Silvi Purnia; Ari Hidayat; Tuti Alawiyah (Universitas Bina Sarana Informatika, 2019)
Abstract: The development of information technology, the need for information systems is very important and necessary in order to facilitate the work of human beings in all fields. Polres Ciamis is a command unit of police officers located in the area of West Java, Indonesia.Bagsumda Polres Ciamis tasked with managing the data proposals promotion from the rank of rank Tamtama, Bintara until Perwira, so far has a computerized system but in the process still has deficiencies in the system, and there are also some processes that are still manual, ranging from the management of proposed promotion data of members of the police of Bintara that are still sought manually so Allows to inhibit in the process of managing visual data of promotion. Therefore, the writer tries to make the final task of app promotion system design at Polres Ciamis with implementation method of Rapid Application Development (RAD) to simplify system development in the process of making the design of this application and simplify in doing further system development. With this promotion app design is expected to simplify and provide data management of promotions with accurate and better. So that it can accelerate the data management promotion of police officers. Keywords: Implementation of RAD Method, Web, Increase System Member of Police of Bintara